2015
DOI: 10.3390/molecules200917429
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Microbial Modulation of the Large Intestine Ecosystem by Non-Absorbed Diet Phenolic Compounds: A Review

Abstract: Phenolic compounds represent a diverse group of phytochemicals whose intake is associated with a wide spectrum of health benefits. As consequence of their low bioavailability, most of them reach the large intestine where, mediated by the action of local microbiota, a series of related microbial metabolites are accumulated. In the present review, gut microbial transformations of non-absorbed phenolic compounds are summarized. Several studies have reached a general consensus that unbalanced diets are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
199
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(214 citation statements)
references
References 192 publications
(404 reference statements)
10
199
0
5
Order By: Relevance
“…Equol has been shown to be more bioactive than its food precursor daidzein in vitro and in trials (predominantly with the equol-producer phenotype assessed retrospectively), the magnitude of the biological effect was greatly enhanced in participants who produced equol after isoflavone ingestion, which suggested that there is a critical role of the microbiome for health effects (125127). In general terms, there is emerging literature that describes the diverse and significant impact of flavonoid phenolics and other small molecules that are produced in the large intestine on physiologic processes such as SCFA production and bioavailability, bile acid metabolism, redox and inflammatory status, and associated intestinal, hepatic, and overall systemic functions (128). The production of SCFA is of interest in colonic health, dietary energy extraction, and body-weight regulation (128, 129).…”
Section: Etiology Of the Heterogeneity In Flavonoid Admementioning
confidence: 99%
See 2 more Smart Citations
“…Equol has been shown to be more bioactive than its food precursor daidzein in vitro and in trials (predominantly with the equol-producer phenotype assessed retrospectively), the magnitude of the biological effect was greatly enhanced in participants who produced equol after isoflavone ingestion, which suggested that there is a critical role of the microbiome for health effects (125127). In general terms, there is emerging literature that describes the diverse and significant impact of flavonoid phenolics and other small molecules that are produced in the large intestine on physiologic processes such as SCFA production and bioavailability, bile acid metabolism, redox and inflammatory status, and associated intestinal, hepatic, and overall systemic functions (128). The production of SCFA is of interest in colonic health, dietary energy extraction, and body-weight regulation (128, 129).…”
Section: Etiology Of the Heterogeneity In Flavonoid Admementioning
confidence: 99%
“…In general terms, there is emerging literature that describes the diverse and significant impact of flavonoid phenolics and other small molecules that are produced in the large intestine on physiologic processes such as SCFA production and bioavailability, bile acid metabolism, redox and inflammatory status, and associated intestinal, hepatic, and overall systemic functions (128). The production of SCFA is of interest in colonic health, dietary energy extraction, and body-weight regulation (128, 129). Although flavonoid-induced effects on the main SCFAs acetic (C2), propionic (C3), and butyric (C4) acids have been repeatedly shown in in vitro fermentation systems and in rodent models (128), data from human interventions have been limited and nonconclusive.…”
Section: Etiology Of the Heterogeneity In Flavonoid Admementioning
confidence: 99%
See 1 more Smart Citation
“…Considering similar effects of polyphenol‐enriched diets in laboratory animals (Larrosa et al., ; Qiao et al., ; Etxeberria et al., ), it can be postulated that a key mechanism of this beneficial effect of polyphenol‐rich diets in pigs is their contribution to gut health by exerting a pre‐biotic activity favouring the growth of beneficial bacteria while inhibiting the growth of pathogenic bacteria. This beneficial modulation of the gut microbiota is known to enhance gut barrier function, decrease the translocation of bacterial components into the circulation and stimulate the host immune system (Mosele et al., ). In line with this, it was reported that the modulation of the colon microbiota by plant polyphenols correlated with reduced levels of systemic inflammatory markers, such as C‐reactive protein, and decreased expression of inflammatory genes in tissues (Axling et al., ; Queipo‐Ortuño et al., ; Moreno‐Indias et al., ).…”
Section: Effects Of Polyphenols On Oxidative Stress and Inflammation mentioning
confidence: 99%
“…and decreased undesirable bacteria such as clostridia after batch culture fermentations [16]. Phenolic compounds contained in a cocoa powder reduced the growth of some members of the genera Staphylococcus and Clostridium, affecting the intestinal microbiota profile [17].…”
Section: Introductionmentioning
confidence: 99%